Nuancing Young Masculinities Helsinki Boys' Intersectional Relationships in New Times - Peltola, Marja (Helsinki University Press, 2022)
Nuancing Young Masculinities tells a complex story about the plurality of young masculinities. It draws on the narratives of Finnish young people (mostly boys) of different social classes and ethnicities who attend schools in Helsinki, Finland. Their accounts of relations with peers, parents, and teachers give insights into boys' experiences and everyday practices at school, home, and in leisure time. The theoretical insights in this volume are wide-ranging, illuminating the plurality of masculinities, their dynamism, and intersections with other social identities. The young people's enthusiastic and reflexive engagement with the research dispels stereotypes of boys and masculinities and offers a unique and holistic re-imagining of masculinities. Nuancing Young Masculinities provides a nuanced and compelling understanding of young masculinities.